Kualitas Tidur Pasien Gagal Jantung - Leni Handayani; Urip Rahayu; Hesti Platini (STIKes Karsa Husada Garut, 2020)
Right heart failure occurs if abnormal underlying primary right ventricles such as pulmonary stenosis pulmonary hypertension against lung thromboembolism that occurs systemic venous congestion. This research method uses descriptive method, sampling by purposive sampling, arrested 62 people. The instrument used was the Pittsburgh Sleep Quality Index (PSQI) questionnaire with a validity of 0.810 and a reliability of 0.42 univariate data analysis. The results of this study indicate that the sleep quality of right heart failure patients largely improves poor sleep quality (79.0%). The conclusion shows the quality of sleep in patients with right heart failure, almost all respondents Suggestions for health facilities are expected to make policies to overcome problems related to sleep comfort for patients with heart failure, for example every nurse provides education to overcome sleep problems in patients with right heart failure.